Analyzing the changing relationship between personal consumption and suicide mortality during COVID-19 pandemic in Japan, using governmental and personal consumption transaction databases - Matsumoto, Ryusuke; Kawano, Yasuhiro; Motomura, Eishi; Shiroyama, Takashi; Okada, Motohiro (Frontiers in Public Health, 2022)
During the early stage of the ongoing COVID-19 pandemic, suicides did not increase in most countries/regions; however, Japan exceptionally displayed increasing females suicide without changing males suicide. To explore the mechanisms of increasing suicides, the fluctuations of personal consumptions (as lifestyles factor) and standardized suicide death rate (suicide-mortality) disaggregated by age, gender, and prefecture, were determined using linear mixed-effect model. Additionally, fixed-effects of personal consumptions on suicide-mortality during the pandemic were also analyzed using hierarchical linear regression models with robust standard errors. During the first wave of the pandemic, suicide mortality for both genders slightly decreased, but increased during the second half of 2020. Suicide-mortality of younger than 70 years old females and younger than 40 years old males continued to increase throughout 2021, whereas suicide-mortality for other ages of both genders did not increase. Personal consumption expenditures on out-of-home recreations (travel agencies, pubs, and hotels) and internet/mobile communication expense decreased, but expenditures on home-based recreations (content distribution) increased during the pandemic. Increasing expenditures on internet/mobile communication expense were related to increasing suicide-mortality of both genders. Increasing expenditures on content distributions were related to increasing females suicide-mortality without affecting that of males. Decreasing expenditures on pubs were related to increasing suicide-mortalities of both genders in non-metropolitan region. These findings suggest that transformed individual lifestyles, extended time at home with decreased outing for contact with others, contributed to progression of isolation as risk of suicide. Unexpectedly, increasing compensatory contact with others using internet/mobile communication enhanced isolation resulting in increased suicide risk.